Soil organic carbon, carbon fractions, and microbial community under various organic amendments - Wu, Baojian; Zhang, Meng; Zhai, Zhen; Dai, Huaxin; Yang, Mengmeng; Zhang, Yangling; Liang, Taibo (Scientific reports, 2024)
The impact of various organic amendments on soil organic carbon (SOC) have rarely been reported. To address this, a laboratory experiment was designed to scrutinize the effects of different amendments on soil carbon fractions, microbial communities, and the underlying interactive mechanisms. The experiment encompassed a no-amendment control (CK), as well as treatments with corn straw (CS), tobacco stalks (TS), and peanut shell biochar (PB). Over a 70-day incubation, the SOC in plots amended with CS, TS, and PB displayed significant boosts of 13.9%, 17.5%, and 44.8%, respectively, compared to the CK. For soil carbon fractions, amendments with PB, TS, and CS led to a dramatic rise in particulate organic carbon (POC) of 27.4%, 20.2%, and 105.7%, respectively, in contrast to the CK plots. Mantel analysis and structural Equation Modeling uncovered strong interrelationships among the cbbL, cbbM , Bacteroidota , TOC, and POC. Organic amendments enhance soil carbon fractions, modulating the microbial community by increasing Bacteroidetes abundance and suppressing Acidobacteria richness, thereby influencing the abundance of key carbon cycle genes such as cbbL and cbbM . These results suggest that the addition of peanut shell biochar significantly boosted TOC and key carbon fractions, enhancing carbon content and soil fertility.